Living Too Long? Exploring Attitudes Toward Reaching 100 Years Old. (June 2018) - Ribeiro, Oscar; Canedo, Sofia; Cerqueira, Margarida; Nascimento, Ana; Teixeira, Laetitia
Objective: This study analyses the relationship between pro- and anti-longevity attitudes, attitudes toward centenarians, and the wish to reach 100 years of age in a sample of community dwelling older adults. Methods: Participants ( N = 137) completed a questionnaire on attitudes toward life-extension and an aging semantic differential using centenarians as an attitudinal target. Sociodemographic information, perceived health status, and information on knowing a centenarian were also obtained. A cluster analysis was used to identify subgroups (leaning anti-longevity group vs. leaning prolongevity group), and their associations with personal attributes were tested using logistic regression models. Results: Most respondents said they would wish to reach 100 years old (54.7%) and presented a leaning positive attitude toward centenarians (52.6%). Holding a negative attitude toward centenarians rather than any other attribute increases the odds of having more negative attitudes toward life extension. Conclusion: Results stress the importance of social views on extreme longevity in shaping life extension attitudes.